Nanopatterning‐Enhanced Sensitivity and Response Time of Dynamic Palladium/Cobalt/Palladium Hydrogen Gas Sensors. Issue 5 (30th June 2016) - Lueng, Chris; Lupo, Pierpaolo; Metaxas, Peter J.; Kostylev, Mikhail; Adeyeye, Adekunle O.
Abstract : Clear advantages of nanopatterned Pd/Co films over continuous Pd/Co films are demonstrated as candidates for future hydrogen gas sensing devices based upon hydrogen‐absorption‐modified ferromagnetic resonance. Nanopatterning results in a higher sensitivity to hydrogen gas and a much faster hydrogen desorption rate. It also avoids the need for an external biasing magnetic field which may be important for practical sensor implementation. A wide range of hydrogen gas concentrations has been detected with the nanopatterned material: from 0.1% to 50%, across the threshold of hydrogen flammability in air (4%). Abstract : Clear advantages of nanopatterned Pd/Co films over continuous ones as candidates for future hydrogen gas sensors based upon hydrogen‐absorption‐modified ferromagnetic resonance are demonstrated. Nanopatterning removes the need for an external biasing magnetic field and results in a higher sensitivity and much faster device response and recovery times. Hydrogen gas concentrations from 0.1% to 50% have been successfully detected.